(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article talks about the implementation of the quality of education in higher education institutions. The quality assurance indicators of the higher education system, the main links of the quality of education and the evaluation of the indicators of the quality and efficiency of education in higher education are mentioned.